“It lives!”: Mary Shelley’s Frankenstein and Its Theatrical Afterlife in the Nineteenth Century - Giles, Isabelle (Romanticism on the Net, 2024)
This article explores the relationship between Mary Shelley’s Frankenstein (1818) and its nineteenth-century dramatisations, particularly the most influential, Presumption; or, The Fate of Frankenstein (1823) by Richard Brinsley Peake. By investigating how the theatrical conventions of the nineteenth-century stage came to define the novel’s wider perception, this article argues that the dramatisations may have inspired Shelley’s revisions for the 1831 edition of the text. These revisions reflect the plays’ thematic preoccupations, even now including the word presumption, which was heavily associated with Peake’s adaptation and its themes of hubris. In such a way, the continuous transformation of Frankenstein as a culture-text has helped it to remain ever present and ever relevant.